Dynamic deep stateful firewall packet analysis model - Kailanya, Eunice; Mwadulo, Mary; Omamo, Amos (African Journal of Science, Technology and Social Sciences, 2022)
Due to challenges of COVID -19 pandemic, network is widely used and more network threats are evolving, therefore, there is a need to improve network tools in order to control threats. Stateful firewall is a network tool that build up packet filters by keeping record of packet passing through the network in a state table, so that when a new packet arrives, the stateful firewall filtering mechanism first checks to determine whether the information is similar to the one in state table, in order to allow or blocked a packet. Although several stateful firewall models have been developed to filter network packets, there is no model that is able to filter the entire parts of a network packet which include the header, trailer and payloads. In the stateful firewall models developed, mixed research methodology have been used. The models are developed in python programming language; an experimental research design is used, string matching and pattern matching algorithms are used in developing the models.